Pengenalan Luka Dan Macam-Macam Luka Dalam Kegiatan Tri Bakti PMR Di SDN Sukabumi I - ., Ani Anjarwati; ., Amalia Hikmatul Jannah; ., Galu Kusuma Dewi Ramadani; ., Masruro; ., Khoirunnisa Rahmatillah; ., Siti Romla (CV. ITTC INDONESIA, 2022)
If the continuity of the cell structure is cut off due to imperfect or missing cell elements, it can cause damage to the protective function of the skin and can be accompanied by damage to other cell elements, which can be called a wound. Wounds can also be accompanied by other tissue damage. Accidents involving moving vehicles, falls, sudden or sharp shocks, and surgical procedures are all potential causes of injury. There may be abrasions, lacerations, bruises, cuts, knife wounds, and gunshot wounds among the several types of injuries that may occur. The purpose of the Tri Bakti activities that researchers carried out at SDN SUKABUMI 1 was to introduce injuries and their various types in PPMR Tri Bakti activities. In various wound problems, wound care generally uses procedures. To ensure the wound healing process goes as it should, wound care must adapt to the circumstances and challenges of the injuries that arise.